The feasibility of performing a randomised controlled trial for femoroacetabular impingement surgery. - Palmer, A; Thomas, G; Pollard, T; Rombach, I; Taylor, A; Arden, N; Beard, D; Andrade, A; Carr, A; Glyn-Jones, S (2013)
OBJECTIVES: The number of surgical procedures performed each year to treat femoroacetabular impingement (FAI) continues to rise. Although there is evidence that surgery can improve symptoms in the short-term, there is no evidence that it slows the development of osteoarthritis (OA). We performed a feasibility study to determine whether patient and surgeon opinion was permissive for a Randomised Controlled Trial (RCT) comparing operative with non-operative treatment for FAI. METHODS: Surgeon opinion was obtained using validated questionnaires at a Specialist Hip Meeting (n = 61, 30 of whom stated that they routinely performed FAI surgery) and patient opinion was obtained from clinical patients with a new diagnosis of FAI (n = 31). RESULTS: Clinical equipoise was demonstrated when surgeons were given clinical scenarios and asked whether they would manage a patient operatively or non-operatively. A total of 23 surgeons (77%) who routinely perform FAI surgery were willing to recruit patients into a RCT, and 28 patients (90%) were willing to participate. 75% of responding surgeons believed it was appropriate to randomise patients to non-operative treatment for ≥ 12 months. Conversely, only eight patients (26%) felt this was acceptable, although 29 (94%) were willing to continue non-operative treatment for six months. More patients were concerned about their risk of developing OA than their current symptoms, although most patients felt that the two were of equal importance. CONCLUSIONS: We conclude that a RCT comparing operative and non-operative management of FAI is feasible and should be considered a research priority. An important finding for orthopaedic surgical trials is that patients without life-threatening pathology appear willing to trial a treatment for six months without improvement in their symptoms.